CLINICAL FEATURES AND SURGICAL TREATMENT OF CONGENITAL CATARACT IN THE FRONT MICROPHTHALMIC EYES - Babajanova, L.Dj.; Karimova, D.B.; Umarova, N.O. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the results of ECE with or without IOL implantation in children with congenital cataracts with concomitant anterior microphthalmos of various degrees. Material and methods: A comprehensive ophthalmological examination of 36 children (59 eyes) was performed. Bilateral process is observed in 23 (46 eyes), unilateral in 13 (13 eyes) children with congenital cataract with concomitant anterior microphthalmos. I degree was detected in 22 (61%) children, II degree – in 9 (25%), III degree – in 5 (14%). The age of patients is from 8 months to 11 years, boys 24 (67%), girls 12 (33%). Results: a classical EEC with simultaneous implantation of a soft IOL was performed on 54 (92%) eyes. In 5 (14%) eyes - without implantation, due to intraoperative complications and the presence of concomitant changes in the posterior eyeball. The softest hydrophobic acrylic IOLs, the most biocompatible for children, were used, which were implanted in 89% into the capsular bag and in 11% into the ciliary groove. Conclusions: The extraction of congenital cataract in the eyes with anterior microphthalmus with simultaneous IOL implantation increases the percentage of achievement of high eye functions in children.